2009
DOI: 10.1158/1940-6207.capr-08-0065
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian Adenocarcinomas in the Laying Hen and Women Share Similar Alterations in p53, ras, and HER-2/neu

Abstract: We examined alterations in the p53 tumor suppressor gene and the ras and HER-2/neu oncogenes in chicken ovarian cancers to determine if these tumors have genetic alterations similar to those in human ovarian adenocarcinomas. Mutations in the p53 tumor suppressor gene and the H-ras and K-ras oncogenes were assessed by direct sequencing in 172 ovarian cancers obtained from 4-year-old birds enrolled at age 2 in two separate 2-year chemoprevention trials. Birds in trial B had approximately twice as many lifetime o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…In addition, the chicken has a high ovulatory rate (daily), raising the possibility that chicken and human OVACs have a common pathogenesis related to ovulation-induced genetic damage to ovarian epithelial cells. Importantly, we have recently shown that chicken ovarian adenocarcinomas have genetic or molecular features that are similar to those of human OVAC (34) and that the prevalence of alterations in p53 in chicken tumors correlated with the number of prior ovulatory events, These findings further support the concept that ovulation with repeated cycles of rupture and repair of the ovarian epithelium may increase the number of proliferative events and genetic errors.…”
Section: Introductionsupporting
confidence: 68%
“…In addition, the chicken has a high ovulatory rate (daily), raising the possibility that chicken and human OVACs have a common pathogenesis related to ovulation-induced genetic damage to ovarian epithelial cells. Importantly, we have recently shown that chicken ovarian adenocarcinomas have genetic or molecular features that are similar to those of human OVAC (34) and that the prevalence of alterations in p53 in chicken tumors correlated with the number of prior ovulatory events, These findings further support the concept that ovulation with repeated cycles of rupture and repair of the ovarian epithelium may increase the number of proliferative events and genetic errors.…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, the sequencing of the chicken genome 10 years ago enabled valuable molecular comparisons with human cases (71). Different biomarkers, such as CA-125, P53 and E-cadherin, were also expressed in EOC in both species (28,(72)(73)(74).…”
Section: Incessant Ovulation Hypothesismentioning
confidence: 95%
“…It is possible that structural differences in the ovarian surface epithelium between mice and humans (27) allow mice to develop a form of ̔resistance̓ against EOC development, despite their significantly higher ovulation rates. Interestingly, it is estimated that the number of ovulations of a 2-year-old hen is similar to the number of ovulations of a woman at menopause (28). The fact that the hen is the only animal model that develops spontaneous EOC suggests similarities in the role of ovulation in the development of the disease between hens and humans.…”
Section: Pathology and Origin Of Eoc In Humansmentioning
confidence: 99%
“…Although most genital organ leiomyomas in laying hens develop from the oviduct VL, occasional oviduct leiomyomas can also be seen [2] . In humans, uterine leiomyomas are the most common type of reproductive tract tumours in women and leiomyomas of the oviduct in sexually mature domestic hens share important features with human uterine leiomyomas [7][8][9] . The high prevalence and ability to induce leiomyomas of the oviduct VL in hens means that this species could be of interest as a model for the study of similar tumours in mammals as well as women because the remarkable similarities between the ovulatory cyles of women and hens [3,[7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%